2022
DOI: 10.1002/adma.202204113
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐Learning Spectral Indicators of Topology

Abstract: Topological materials discovery has emerged as an important frontier in condensed matter physics. While theoretical classification frameworks have been used to identify thousands of candidate topological materials, experimental determination of materials’ topology often poses significant technical challenges. X‐ray absorption spectroscopy (XAS) is a widely used materials characterization technique sensitive to atoms’ local symmetry and chemical bonding, which are intimately linked to band topology by the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 82 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…The lack of knowledge of the geometry of the catalyst-support sites hampers such studies in which atomically dispersed catalysts of size-selective clusters are analyzed by “inverting” their XANES spectra. This method opens a new opportunity for structural analysis of such photocatalysts using a machine learning approach. , Namely, multiple spectra calculated theoretically may be used for training a neural network classifier, similar to an analogous approach developed recently for predicting new topological insulators . Such a classifier will be used for interpreting the spectra of different hybrid photocatalysts in terms of different classes of local structure and local geometry of the support, for subsequent structural refinement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of knowledge of the geometry of the catalyst-support sites hampers such studies in which atomically dispersed catalysts of size-selective clusters are analyzed by “inverting” their XANES spectra. This method opens a new opportunity for structural analysis of such photocatalysts using a machine learning approach. , Namely, multiple spectra calculated theoretically may be used for training a neural network classifier, similar to an analogous approach developed recently for predicting new topological insulators . Such a classifier will be used for interpreting the spectra of different hybrid photocatalysts in terms of different classes of local structure and local geometry of the support, for subsequent structural refinement.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Namely, multiple spectra calculated theoretically may be used for training a neural network classifier, similar to an analogous approach developed recently for predicting new topological insulators. 71 Such a classifier will be used for interpreting the spectra of different hybrid photocatalysts in terms of different classes of local structure and local geometry of the support, for subsequent structural refinement. In comparison, current efforts are mostly limited to chemometrics-based approaches and require a large number of experimental spectra for such a classification.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, integrating ML with experiments offers an alternative pathway to augment the capability of experimental techniques for throughput and accuracy [189,190]. For instance, it has been shown that the experimental spatial resolution to identify proximity effect -one key approach to realize TSC -can be enhanced by a factor of two through ML-based analysis [191].…”
Section: Future Prospectivementioning
confidence: 99%
“…An alternative approach is therefore necessary. In particular, feature extraction from spectra data is perhaps the key to machine learning training. , For instance, peak heights, width, numbers of peaks, and slope can be extracted as descriptors and used during training. Furthermore, it is also demonstrated that semi-supervised machine learning can be implemented to classify the crystal structure .…”
mentioning
confidence: 99%